Ekplorasi Interior Cafe Bergaya Vintage di Surabaya - Marcherita Angelia; Yusita Kusumarini; filipus priyo suprobo (Intra, 2014)
This study was conducted to determine the style of design information and applied scientific of Vintage style on interior of the cafe in Surabaya object as an object of research and publications. The method used is descriptive qualitative triangulation techniques supported by collecting multiple sources of scientific and popular literature to find a sense of style Vintage design. The results of this study found scientific sense style Vintage design and applied of Vintage style to interior cafe in Surabaya, then publishes reportage Vintage style cafe interior with popular books and mini movies as a means of education and information regarding the style Vintage design and applied to the interior of the cafe in Surabaya.